Edukasi, Simulasi dan Demonstrasi Cuci Tangan Pakai Sabun dan Menyikat Gigi pada Siswa Sekolah Dasar - Taufiq, Said; Agustina, Fitriani; Fauzi, M Jamil; Yusnidaryani, Yusnidaryani (Jurnal Abdimas Kesehatan (JAK), 2025)
Hygiene and health issues in school-age children are still a concern for health workers, due to low awareness of washing hands with soap and brushing teeth. One of the efforts that can be done is education, simulation and demonstration of the practice of washing hands with soap and brushing teeth properly. Community service activities aim to increase students' knowledge and the formation of clean and healthy living behaviors, especially the behavior of washing hands with soap and brushing the teeth of students at SDN 5 Pirak Timu, North Aceh Regency. The place for the service is Public Elementary School 5 Pirak Timu, North Aceh Regency from August 24 to 27, 2022. The target is students in grades IV to VI with a total of 48 people. Implementation of activities in the form of education about hand washing with soap and brushing teeth followed by simulations and demonstrations of washing hands with soap and brushing teeth properly. Assessment of students' knowledge and skills is carried out before and after being given and demonstrations. The materials used in the implementation of the activities are modules, leaflets and posters. The result achieved was an increasing the knowledge of the target audience about washing hands with soap and brushing teeth. The skills of washing hands with soap and brushing teeth also improved after the simulation and demonstration were carried out. In conclusion. The result achieved is increasing the knowledge of the target audience about washing hands with soap and brushing teeth